Analisis Persepsi Tentang Tax Education Dan Peran Sikap Religiusitas Terhadap Perilaku Kepatuhan Kewajiban Perpajakan - Bahtiar Effendi; Wardah Nabila; Fina Ummiyatul Izza (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
The purpose of this research is to ascertain how is the tax education, the religious attitude of students in carrying out their obligations towards taxation if later they become taxpayers because they have fulfilled the requirements as taxpayers and the factors that influence it. The research approach uses quantitative research methods by conducting a survey of UIN K.H. Abdurrahman Wahid Pekalongan who has received lecture material on taxation. The sampling technique used was non-probability sampling with a quote sampling method. The data analysis method used multiple regression analysis to test the data obtained from the respondents. The research findings provide an analysis that student taxation education affects tax compliance, student religious attitudes affect tax compliance. The novelty in this study is to include the religiosity variable as the attitude of the taxpayer in carrying out tax obligations.